Patirties problema E. Voegelino filosofijoje. - Caturianas, Dovydas (Problems / Problemos, 2021)
The paper deals with the problem of E. Voegelin's notion of experience: the positive meaning of this concept is not specified in any of the author's works. Based on W. James's "Essay on Radical Empiricism" and Voegelin's late works, it is shown that Voegelin's theory of consciousness is rooted in James's concept of "pure experience", which essentially sought to close the epistemological chasm between subject and object, phenomena and noumena. According to this notion, mental and physical, subjective and objective realities are merely derivative aspects of a certain primordial pure experience, which is more elementary and fundamental than the two former aspects of reality. Finally, the article exposes other implications of this connection with James's philosophy for E. Voegelin's theory of consciousness.